2020
DOI: 10.1073/pnas.1913922117
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic afferents from the dorsal raphe decrease the excitability of pyramidal neurons in the anterior piriform cortex

Abstract: The olfactory system receives extensive serotonergic inputs from the dorsal raphe, a nucleus involved in control of behavior, regulation of mood, and modulation of sensory processing. Although many studies have investigated how serotonin modulates the olfactory bulb, few have focused on the anterior piriform cortex (aPC), a region important for olfactory learning and encoding of odor identity and intensity. Specifically, the mechanism and functional significance of serotonergic modulation of the aPC remain lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 51 publications
5
24
0
Order By: Relevance
“…The elevated plus maze test was conducted as previously described to assess anxiety-like behaviors (57). The elevated plus maze consists of two open arms with 3-cm tall ledges and two closed arms (25 × 5 cm) with 15-cm tall transparent walls.…”
Section: Elevated Plus Maze Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevated plus maze test was conducted as previously described to assess anxiety-like behaviors (57). The elevated plus maze consists of two open arms with 3-cm tall ledges and two closed arms (25 × 5 cm) with 15-cm tall transparent walls.…”
Section: Elevated Plus Maze Testmentioning
confidence: 99%
“…The OSNs is thus directly exposed to different external environmental toxins, making them readily insultable and the connected OB susceptible to inflammation. Moreover, the olfactory system is a highly evolved and complex neural network that communicates with different brain regions (57). This system can receive direct projections from the SN to the OB and send information to the SN by multisynaptic transmission (19).…”
Section: Introductionmentioning
confidence: 99%
“…However, with spike/LFP recording there is no direct genetic evidence to prove that the recorded spikes are from M/Ts rather than other cell types, although indirect evidence can be provided by the firing properties [25][26][27]. Fiber photometry has been used in the OB and piriform cortex to investigate neural responses to odor stimulation under different brain states [6,[28][29][30]. In the OB, robust odor-evoked responses are recorded in M/Ts and granule cells [6,28].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the excitatory responses recorded in this study mainly reflect the cortical feedback input from the olfactory cortex onto GCs. Our previous studies have shown that odors always evoke excitatory responses in the pyramidal neurons of the piriform cortex (Zhou et al, 2017;Wang et al, 2020). Given that granule cells in the OB receive extensive glutamatergic feedback from the olfactory cortex (Boyd et al, 2012), the excitatory response in GCs mainly derive from the olfactory cortex.…”
Section: Discussionmentioning
confidence: 98%
“…Fiber photometry was performed using a previously described system (Zhou et al, 2017;Sun et al, 2019;Wang et al, 2019Wang et al, , 2020Wu et al, 2020). To record fluorescent signals, the beam from a 488 nm laser (OBIS 488LS, Coherent) was reflected by a dichroic mirror (MD498, Thorlabs), focused by an objective lens (10×, NA: 0.3; Olympus), and then coupled to an optical commutator (Doric Lenses).…”
Section: Fiber Photometry Recordingmentioning
confidence: 99%